1995
DOI: 10.1172/jci117865
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mice expressing the human heat shock protein 70 have improved post-ischemic myocardial recovery.

Abstract: Heat shock treatment induces expression of several heat shock proteins and subsequent post-ischemic myocardial protection. Correlations exist between the degree of stress used to induce the heat shock proteins, the amount of the inducible heat shock protein 70 (HSP70) and the level of myocardial protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
253
0
18

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 529 publications
(280 citation statements)
references
References 36 publications
9
253
0
18
Order By: Relevance
“…Glucose-insulin-potassium infusion improves the survival of patients with ischemic heart disease, partially because of enhanced glucose uptake and glycolysis by the ischemic myocardium (1). Studies in transgenic mice overexpressing HSP70 and in rats that had received HSP70 expression vectors also indicate that this protein protects myocardium against ischemiareperfusion injury (17,24,26,29,31). Recently we reported (18) that in human fetal cardiac cells, adenovirus-mediated expression of HIF-1␣/VP16 upregulated VEGF, Glut-1, Glut-3, IGFBP-3, gp130, survivin, TNF-␣-inducible protein, and glycolytic enzymes.…”
Section: Fig 1 Effects Of Preconditioning (Pc) On Cell Viability (Amentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose-insulin-potassium infusion improves the survival of patients with ischemic heart disease, partially because of enhanced glucose uptake and glycolysis by the ischemic myocardium (1). Studies in transgenic mice overexpressing HSP70 and in rats that had received HSP70 expression vectors also indicate that this protein protects myocardium against ischemiareperfusion injury (17,24,26,29,31). Recently we reported (18) that in human fetal cardiac cells, adenovirus-mediated expression of HIF-1␣/VP16 upregulated VEGF, Glut-1, Glut-3, IGFBP-3, gp130, survivin, TNF-␣-inducible protein, and glycolytic enzymes.…”
Section: Fig 1 Effects Of Preconditioning (Pc) On Cell Viability (Amentioning
confidence: 99%
“…Activation of protein kinase C (4), protein tyrosine kinases (16), and mitogen-activated protein kinases (33) by these triggers leads to increased expression of the mediators of the late phase of preconditioning. Myocardial protein synthesis of several mediators (or effectors), including inducible NO synthase (iNOS), cyclooxygenase-2 (COX-2), aldose reductase, antioxidant enzymes, and heat shock proteins (HSPs), and activation of ATP-sensitive K ϩ (K ATP ) channels play a critical role in late-phase preconditioning (8,15,21,23,24,29). It has been proposed that activator protein 1 (AP-1) and nuclear factor-B (NF-B) may mediate the transcriptional activation of iNOS, COX-2, aldose reductase, and other genes (22,36).…”
mentioning
confidence: 99%
“…The geese heart Hsp70 expression increased under heat stress suggesting that HSP70 had a protective function in cells . Overexpression of Hsp70 is associated with myocardial protection (Plumier et al 1995;Jayakumar et al 2001;Liu et al 2007). Hao et al (2010) reported the effect of transport stress on variation in the expression of Hsp27, Hsp70, and Hsp90, and the results suggested that Hsps could protect cardiac muscle cells from transport stress.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Hsps, and of Hsp72 in particular, has been shown to protect cells and tissues during episodes of stress (Johnston and Kucey 1988;Riabowol et al 1988;Karmazyn et al 1990;Li et al 1991;Plumier et al 1995). The exact mechanism by which Hsps provide protection remains unknown, but it is thought to relate to their ability to act as molecular chaperones.…”
Section: Introductionmentioning
confidence: 99%